FENOMENA WAITHOOD DAN PERGESERAN NILAI PERNIKAHAN: STUDI SOSIAL MASYARAKAT PERKOTAAN YOGYAKARTA - Qowwim Arfi'atus Salisa (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
The phenomenon of waithood or delayed marriage has become a new social trend among urban youth, including in Yogyakarta City. This article examines the factors contributing to waithood and how this phenomenon reflects a shift in marriage values within Yogyakarta's urban society. The study employs a qualitative-descriptive approach using phenomenological methods and James S. Coleman's Rational Choice Theory. Data were collected through interviews with 50 respondents aged 23-35 years who have not yet married. The findings reveal five main reasons for delaying marriage in Yogyakarta: economic instability, focus on education and career, fear of commitment, difficulty finding a compatible partner, and the influence of social media. Analysis based on Coleman's theory shows that individuals, as social actors, seek to maximize benefits by postponing marriage until they reach ideal financial and emotional conditions. These collective decisions form a new social pattern that indicates a shift in the perception of marriage from a moral obligation to a rational life choice. Therefore, adaptive responses from family, state, and religious institutions are necessary to develop social policies that are more contextual and responsive to the realities of Yogyakarta's urban youth today.Keywords: Waithood, Youth, Value Shift.